Leadership, Work Environment, and Employee Performance at Wamena Regional General Hospital: A Study Using SEM-PL Method - Lourdes Joanna Kusumadi; Agiona Angeline (Journal of Social Research, 2026)
Employee performance is a key indicator of successful hospital management in delivering high-quality health services. Public hospitals, including RSUD Wamena, face complex challenges related to leadership and work environment due to limited resources, geographical conditions, and organizational dynamics. This study aims to analyze the influence of leadership and work environment on employee performance at RSUD Wamena using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. This study employed a quantitative method with an explanatory research design. Data were collected through questionnaires distributed to 150 employees of RSUD Wamena, including medical and non-medical staff. Data analysis was conducted using SEM-PLS with SmartPLS software. Leadership and work environment were treated as independent variables, while employee performance was the dependent variable. The results indicate that leadership has a positive and significant effect on employee performance. The work environment also shows a positive and significant influence on employee performance. Simultaneous testing confirms that leadership and work environment together explain a substantial proportion of the variance in employee performance. These findings emphasize the importance of effective leadership and a supportive work environment in enhancing employee performance in public hospitals. This study is expected to provide practical contributions for hospital management in formulating human resource management policies, particularly in strengthening leadership capacity and improving the work environment.